MANAJEMEN BURSA KERJA KHUSUS SMK MA’ARIF NU 01 LIMPUNG KABUPATEN BATANG - Srianah; Noor Miyono; Rasiman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Vocational High Schools (SMK) have the responsibility to prepare reliable middle-level Human Resources, oriented to the needs of the job market and prepare graduates ready for work. Vocational Schools' efforts to overcome unemployment are holding a Special Job Fair (BKK) program. The aim of this research is to analyze the management of BKK SMK Ma'arif NU 01 Limpung, Batang Regency, namely 1) planning, 2) organizing, 3) implementing, 4) controlling. This research is qualitative research with a descriptive approach. This research was conducted at the BKK managed by SMK Ma'arif NU 01 Limpung, Batang Regency. Research data collection techniques include observation, interviews, document review. Test the validity of the data using source triangulation technical. The research results show that 1) Special job market planning includes needs analysis planning, socialization of activities and determining sources/funding for the BKK program. 2) Organizing BKK includes industrial/DUDI cooperation, competency standardization and selection of managers who are competent and have integrity, 3) Implementation of special job fairs including offering graduates, providing guidance, recruitment, job fairs and graduate searches 4) Supervising special job fairs by monitoring together with DUDI and evaluate the implementation of the BKK program on an ongoing basis. Suggestions and recommendations 1) it is necessary to increase the consistency of BKK officers in providing soft-skills training and additional skills training. 2) SOPs need to be prepared for BKK management and implemented collaboratively between schools and DUDI.